99.5k views
4 votes
(3a) (a^-3) please help I'm very confused if possible please show your work! <:D

User Mejonzhan
by
4.7k points

1 Answer

1 vote


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ (3a)(a^(-3))\implies 3a\cdot \cfrac{1}{a^3}\implies \cfrac{3a}{a^3}\implies \cfrac{3~~\begin{matrix} a \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{aa~~\begin{matrix} a \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies \cfrac{3}{a^2}

User Gregavola
by
4.9k points